2014
DOI: 10.17221/7684-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Glucan on cold-stress resistance of striped catfish, Pangasianodon hypophthalmus (Sauvage, 1878)

Abstract: ABSTRACT:These experiments were performed to determine the effects of dietary β-glucan on stress responses of striped catfish (Pangasianodon hypophthalmus). Fish were fed for nine weeks with a diet containing 0 (control), 0.5% (G1), 1% (G2) and 2% (G3 group) β-glucan. Subsequently, stress responses were studied by evaluating serum cortisol and glucose levels following a constant 24 h cold shock (from 28 °C to 15 °C). Serum cortisol and glucose concentrations were measured after cold treatments of varying durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 59 publications
2
13
0
1
Order By: Relevance
“…In rainbow trout, physiological cortisol serum levels did not change in fish fed with 0.1% of βglucan during four weeks [26]. Similarly, Pangasianodon hypophthalmus fed with different concentrations of β-glucan during 9 weeks also did not show changes in the levels of circulating cortisol [27]. We observed that in matrinxã fed with β-G 2 high levels of cortisol were maintained at 6 hpi.…”
Section: Discussionmentioning
confidence: 52%
“…In rainbow trout, physiological cortisol serum levels did not change in fish fed with 0.1% of βglucan during four weeks [26]. Similarly, Pangasianodon hypophthalmus fed with different concentrations of β-glucan during 9 weeks also did not show changes in the levels of circulating cortisol [27]. We observed that in matrinxã fed with β-G 2 high levels of cortisol were maintained at 6 hpi.…”
Section: Discussionmentioning
confidence: 52%
“…Many studies have shown that b-glucan plays an important role in activating the immune system (Sirimanapong et al 2015;Miest et al 2016) and conferring the protection against various stress reactions in aquatic animals (Barros et al 2014;Soltanian et al 2014;Dawood et al 2015). It is well known that the enhancement of stress resistance has been closely linked to improving energy metabolism (Lushchak 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There seems to be a dose‐dependent effect when β‐glucans are orally administered with the feed. The optimal level for pampona fish ( Trachinotus ovatus ) and striped catfish ( Pangasianodon hypothalamus ) seems to lie between 0.5 and 1 g/kg of feed (Soltanian, Adloo, Hafeziyeh, & Ghadimi, ; Huu et al., ). In the present study, common carp were fed with a diet supplemented with 1% MacroGard ® , which might be a proper concentration for positive effects of β‐glucans.…”
Section: Discussionmentioning
confidence: 99%